Do prosthetic limbs really have to cost an arm and a leg? - Shahzada, Haashim; Mohammed, Samiuddin; Nigm, Mohammed; Niaz, Adeel; Khilji, Yousuf; Ali, Hashim; Zuberi, Abdul Nafea; Allam, Ahmed; Hajjaj, Abdulrahman (The Meducator, 2022)
With the average cost of commercially available prosthetics ranging from 4,000 to 75,000 CAD, these essential devices are inaccessible to physically disabled people. Production expenses of the various prosthesis types required for each individual’s functional needs will continue increasing in coming years. This is one of the many factors that contributes to health inequities affecting those with physical disabilities in the Canadian healthcare system. Prosthesis coverage across the country is highly variable; many individuals are forced to rely on personal resources, fundraising, or contributions from non-governmental organizations (NGOs) to meet this basic healthcare need. The Institute for Research on Public Policy and Statistics Canada reports that disabled individuals are more likely to be unemployed, have lower median incomes, and be less likely to graduate with a university degree than those without a disability, further contributing to this disparity. As a team, we address the cost barrier of prostheses by establishing Brachïum: a humanitarian initiative focused on creating an affordable, 3D printed, open-source transradial prosthesis prototype that could eventually be distributed to marginalized communities to improve their quality of life.